Unveiling the Antimicrobial, Anti-Biofilm, and Anti-Quorum-Sensing Potential of Paederia foetida Linn. Leaf Extract against Staphylococcus aureus: An Integrated In Vitro-In Silico Investigation - Sirijan Santajit; Witawat Tunyong; Dararat Horpet; Asma Binmut; Thida Kong-Ngoen; Churaibhon Wisessaowapak; Techit Thavorasak; Pornpan Pumirat; Nitaya Indrawattana (MDPI AG, 2024)
Antimicrobial resistance poses a global health threat, with Staphylococcus aureus emerging as a notorious pathogen capable of forming stubborn biofilms and regulating virulence through quorum sensing (QS). In the quest for novel therapeutic strategies, this groundbreaking study unveils the therapeutic potential of Paederia foetida Linn., an Asian medicinal plant containing various bioactive compounds, contributing to its antimicrobial activities, in the battle against S. aureus. Through a comprehensive approach, we investigated the effect of ethanolic P. foetida leaf extract on S. aureus biofilms, QS, and antimicrobial activity. The extract exhibited promising inhibitory effects against S. aureus including the biofilm-forming strain and MRSA. Real-time PCR analysis revealed significant downregulation of key virulence and biofilm genes, suggesting interference with QS. Biofilm assays quantified the extract's ability to disrupt and prevent biofilm formation. LC-MS/MS analysis identified quercetin and kaempferol glycosides as potential bioactive constituents, while molecular docking studies explored their binding to the QS transcriptional regulator SarA. Computational ADMET predictions highlighted favorable intestinal absorption but potential P-glycoprotein interactions limiting oral bioavailability. While promising anti-virulence effects were demonstrated, the high molecular weights and excessive hydrogen bond donors/acceptors of the flavonoid glycosides raise concerns regarding drug-likeness and permeability. This integrated study offers valuable insights for developing novel anti-virulence strategies to combat antimicrobial resistance.